2021
DOI: 10.1038/s41598-021-99983-6
|View full text |Cite|
|
Sign up to set email alerts
|

A beneficial role of computer-aided diagnosis system for less experienced physicians in the diagnosis of thyroid nodule on ultrasound

Abstract: Ultrasonography (US) is the primary diagnostic tool for thyroid nodules, while the accuracy is operator-dependent. It is widely used not only by radiologists but also by physicians with different levels of experience. The aim of this study was to investigate whether US with computer-aided diagnosis (CAD) has assisting roles to physicians in the diagnosis of thyroid nodules. 451 thyroid nodules evaluated by fine-needle aspiration cytology following surgery were included. 300 (66.5%) of them were diagnosed as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Many studies have shown that the CAD system is more beneficial for junior radiologists to improve their diagnostic performance ( 32 34 ), which was also confirmed in our study. In this study, we used ACR TI-RADS TR4 and TR5 as the cutoff values separately and found that the AUC of the CAD system was higher than that of both junior and senior radiologists when TR4 was used as the cutoff value, and the specificity of the radiologists was lower than that of the CAD system.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown that the CAD system is more beneficial for junior radiologists to improve their diagnostic performance ( 32 34 ), which was also confirmed in our study. In this study, we used ACR TI-RADS TR4 and TR5 as the cutoff values separately and found that the AUC of the CAD system was higher than that of both junior and senior radiologists when TR4 was used as the cutoff value, and the specificity of the radiologists was lower than that of the CAD system.…”
Section: Discussionsupporting
confidence: 89%
“…Conventional ultrasound examination has many advantages, such as safety, low costs, simple to use, repeatable, and no radioactivity, and thus, has been widely used in clinical practice (10)(11)(12). Conventional ultrasound images of thyroid malignant nodules are characterized by irregular shape, unclear edge, non-uniformity, microcalcification, low echo, and aspect ratio greater than 1 (13). However, conventional ultrasound has great limitations in the diagnosis of clinically complicated benign and malignant thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies on computer-aided diagnoses of disorders, including thyroid diseases, have been carried out. It is reported that computer-aided diagnosis can offer efficient dataset processing, accurate diagnosis, clinical decision-making support, and even potential treatment options for thyroid diagnosis (27)(28)(29)(30). Computer-aided diagnosis of HT has been In this study, we collected fifteen clinical characteristics and laboratory data to study their significant correlations with HT and thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%